2010
DOI: 10.30552/ejep.v3i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Creación de metáforas: ¿Una medida de creatividad o inteligencia?

Abstract: El objetivo del presente estudio fue comprobar si el "Test de creación de metáforas" sería realmente una medida con características únicas de la creatividad, o una manera diferente de evaluar constructos ya conocidos como la inteligencia. Se consideraron dos grupos diferenciados: el grupo 1 estaba formado por 90 estudiantes mayores en un programa de educación de adultos, y el grupo 2 incluyó a 73 estudiantes universitarios de las titulaciones de Arquitectura y Urbanismo. Los resultados mostraron correlaciones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In recent years, there has been an interest in exploring the underlying cognitive processes involved in figurative language comprehension ( Chiappe and Chiappe 2007 ; Pereira de Barros et al 2010 ; Pierce and Chiappe 2009 ; Silvia and Beaty 2012 ). In this light, some studies suggest connecting the comprehension of figurative language to the CHC model of cognitive abilities.…”
Section: Attempting To Integrate Figurative Language Comprehension In...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been an interest in exploring the underlying cognitive processes involved in figurative language comprehension ( Chiappe and Chiappe 2007 ; Pereira de Barros et al 2010 ; Pierce and Chiappe 2009 ; Silvia and Beaty 2012 ). In this light, some studies suggest connecting the comprehension of figurative language to the CHC model of cognitive abilities.…”
Section: Attempting To Integrate Figurative Language Comprehension In...mentioning
confidence: 99%
“…They also perform better in various creative tasks, such as divergent thinking ( Silvia et al 2009 ) and humor production ( Nusbaum et al 2017 ; Sutu et al 2019 ). In general, research has predominantly demonstrated that the generation of creative metaphors incorporates cognitive functions like fluid intelligence as well as personality traits that facilitate creative thinking and creative problem solutions, such as Openness ( Beaty and Silvia 2013 ; Pereira de Barros et al 2010 ) and the need for cognition ( Watts et al 2017 ). Whether such a relation also occurs for figurative language comprehension will be tested here.…”
Section: Considering Personality For the Comprehension Of Figurative ...mentioning
confidence: 99%
See 1 more Smart Citation
“…El proceso janusiano de pensamiento ha sido otro de los estudiados en la literatura (ej. Rothenberg et al, 1999;Sak, 2009); También ha sido muy estudiado el proceso del pensamiento metafórico (de Barros et al, 2010). Finalmente, son muy conocidos los estudios sobre la representación del problema (Arreola y Reiter-Palmon, 2016) o la integración de conceptos (Birdsell, 2019).…”
Section: Introductionunclassified
“…Finally, we realized that instructors who used more similes and metaphors in their videos had a higher tendency to use more words that express cognitive processes (e.g., cause, know, think); see figure 6. Several studies have identified the underlying cognitive processes involved in using figurative language [41,42,43]. relationship between use of simile (figurative language) and cognitive processes.…”
Section: Quantitative Analysismentioning
confidence: 99%